Penerapan Business Intelligence dalam Pengambilan Keputusan Bisnis: Studi Pendekatan Praktis untuk UMKM di Indonesia - Angkasa, Pramuja; Nasution, Muhammad Irwan Padli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Business Intelligence (BI) is a technology and data analysis process that helps organizations make business decisions more accurately and quickly. In today’s digital era, BI has become an important tool even for small businesses such as MSMEs. This study aims to explain the basic concept of BI, its benefits, and provide examples of its practical application for MSMEs. The results of the analysis show that the use of BI can improve operational efficiency and accuracy in marketing strategies and financial planning.